On the Relation between Leadership and Positive Psychological Capital in the Hospitality Industry - Harun Şeşen; Lütfi Sürücü; Ahmet Maşlakcı (International Journal of Business, 2019)
This study aims to analyze the relation between leadership and positive psychological capital (PsyCap) in the hospitality industry. Questionnaires were applied to employees of five-star hotels operating in the Turkish Republic of Northern Cyprus selected by a sampling method (N = 372). The obtained data were analyzed using IBM SPSS 23. There are many studies on PsyCap and leadership, concentrating on the factors of organizational commitment, job satisfaction, and the organizational dimension. Research has increasingly explored the effects of PsyCap, leadership, job empowerment, and employee participation, while empirical sectorial studies that overlook comprehensive and dynamic relationships remain limited (Joo, Lim and Kim, 2016). This study aims to contribute to the literature with this dimension. The results of the research show that transformational leadership has a positive effect on PsyCap, while laissez-faire leadership has a significant and negative effect and transactional leadership has no effect.
Keywords: D23; L83; M12; 330; leadership; leadership styles; positive psychological capital